Construct Validity and Differential Item Functioning of the PHQ-9 Among Health Care Workers: Rasch Analysis Approach - Jiraniramai, Surin (Neuropsychiatr Dis Treat, 2021)
PURPOSE: The Patient Health Questionnaire (PHQ-9) is a widely used self-report questionnaire to screen depression. Its psychometric property has been tested in many populations including health care workers. We used Rasch measurement theory to examine the psychometric properties of PHQ-9 regarding item difficulty, item fit and the differences between subgroups of respondents classified by sex, age, education and alcohol user status, based on the same overall location of participants. PATIENTS AND METHODS: In total, 3204 health care workers of Maharaj Nakorn Chiang Mai Hospital participated and were administered the PHQ-9. Rating scale Rasch measurement modeling was used to examine the psychometric properties of the PHQ-9. RESULTS: The data fitted well to the Rasch model and no violations of the assumption of unidimensionality were observed. All 9 items could form a unidimensional construct of overall depressive severity. Suicidal ideation was the least endorsed while sleep problem was the most. No disordered category and threshold of the rating response were observed. No locally dependent items were observed. No items were found to show differential item functioning across age, sex, education and alcohol consumption. The item-person Wright map showed that the PHQ-9 did not target well with the sample, and a wide gap suggesting few or no items exist to differentiate participants at a certain ability level among the PHQ-9 items. CONCLUSION: The PHQ-9 can be used as a screening questionnaire for major depressive disorder as its psychometric property was verified based on Rasch measurement model. The findings are generally consistent with related studies in other populations. However, the PHQ-9 may be unsuitable for assessing depressive symptoms among health care workers who have low levels of depression.